Mosquito Repellents - Cynthia Roxanne Rutledge-Connelly (EDIS, 2002)
This document is Fact Sheet ENY-671, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Serivce, Institute of Food and Agricultural Sciences, University of Florida. Date first published: September 2002.